Geostrophic and Mesoscale Eddy Contributions to the Atlantic Meridional Overturning Circulation Decline Under CO2 Increase in the GFDL CM2-O Model Suite - Fortin, Anne-Sophie; Dufour, Carolina, O; Merlis, Timothy; Msadek, Rym (Journal of Climate, 2023)
The pattern and magnitude of the Atlantic meridional overturning circulation (AMOC) in response to an increase in atmospheric carbon dioxide (CO 2 ) concentration greatly differ across climate models in particular due to differences in the representation of oceanic processes. Here, we investigate the response of the AMOC to an idealized climate change scenario, along with the drivers of this response, in the three configurations of a coupled climate model suite with varying resolutions in the ocean (1°, 0.25°, 0.10°). In response to the CO 2 increase, the AMOC shows a reduction of similar magnitude in the low and high resolutions, while a muted response is found in the medium resolution. A decomposition of the AMOC into its geostrophic and residual components reveals that most of the AMOC reduction is due to a weakening of the geostrophic streamfunction driven by temperature anomalies, partly opposed by a strengthening of the geostrophic streamfunction driven by salinity anomalies. Changes in the AMOC due to the mesoscale eddy streamfunction contribute to 13% and 17% of the AMOC decline in the low and high resolutions, respectively, but induce very little change in the medium resolution. The similar response of the AMOC strength in the low and high resolutions hides important differences in the contribution and pattern of the geostrophic and eddy streamfunctions. The lack of sensitivity of the medium resolution to the CO 2 forcing is due to a weak connection between the deep water formation regions in the northern subpolar gyre and the Deep Western Boundary Current. Significance Statement The Atlantic meridional overturning circulation (AMOC) is a major system of ocean currents in the Atlantic that contributes to shaping the climate at regional and global scales, notably through the transport of heat from the low to the high latitudes. A major slowdown of the AMOC over the twenty-first century is predicted by current climate models in response to increasing greenhouse gases. Yet, the magnitude and timing of this ...